Case Report: Mutation in TNNI3(c. 544G>A): a novel likely pathogenic mechanism of neonatal dilated cardiomyopathy - Li, Xianhong; Dai, Liying; Zhang, Jian (Frontiers in Pediatrics, 2023)
Background: Dilated cardiomyopathy (DCM) is a rare disease that causes heart failure due to malfunction of the heart muscle characterized by left ventricular dilation and poor systolic function. Genetic screening leads to advantages in early diagnosis and prognostic assessment of patients with suspected inherited cardiomyopathies. Here, we report a case of neonatal dilated cardiomyopathy due to a mutation of the TNNI3 gene, which has not been published in neonatal dilated cardiomyopathy before.The patient was a22-day-old newborn boy with poor ability to respond to stimuli, presenting with shortness of breath over 11 days. He presented with irregular fever, tachypnea, difficulty in ventilator withdrawal, and mild edema of both lower limbs, and III/6SM could be heard in the precardiac area. He presented repeated weaning difficulties during hospitalization with intractable low EF heart insufficiency. Doppler echocardiography showed refractory low ejection fraction, cardiac enlargement, cardiac insufficiency, mild pulmonary hypertension, and mitral and tricuspid insufficiency with mild valve regurgitation. Whole-exome sequencing showed a mutation in the TNNI3 gene, c. 544G>A (p.Glu182Lys). Thus, he was diagnosed with neonatal DCM. There was no mutation in the parents, The child died 2 weeks after discharge.